Empirical approach to the gender gap in students’ reading consumption in international contexts - Trigo Ibáñez, Ester; Santos Díaz, Inmaculada Clotilde (Frontiers in Psychology, 2023)
Reading is a very important aspect today, which is why it is a recurring topic in research. This study aims to analyze the gap between the reading consumption of adolescents by sex and compare the situation in Spain with that of other countries. It is based on the hypothesis that reading consumption is conditioned by sex and the educational policies of the countries and, therefore, by the place where the study is carried out. This research addresses, for the first time, the influence of the sex factor on the reading habits of adolescents who have just begun their training in secondary education. To do this, an international sample of students has been taken as a reference, made up of a matrix group of Spanish students that is contrasted with small samples from three different countries that we are interested in comparing with the Spanish context. These are Portugal, Poland, and Chile. This is an empirical study carried out based on the research projects: "Determining factors in the reading habits of secondary education students. A study from the variables of the educational context" and "Reading habits in international contexts of Secondary Education students. A study of educational practices to promote reading". The results have shown that the gender gap in reading is perceived in all the contexts studied and that it increases in contexts with less developed co-education programs, hence it is necessary to implement effective policies, from the educational field, to alleviate the existence of sexual stereotypes.